EFFECTIVE STRATEGIES FOR FOSTERING CREATIVITY IN THE CLASSROOM: APPROACHES AND IMPLICATIONS FOR EDUCATORS - Turaboyeva Khumora (Web of Journals Publishing, 2024)
This article explores methods to enhance creativity in the classroom. Creativity is vital for student development, but it often remains underdeveloped in traditional educational settings. This research examines various strategies, including fostering a supportive environment, encouraging open-ended problem-solving, integrating technology, and adopting student-centered teaching methods. The results suggest that fostering a creative classroom requires a multifaceted approach, integrating both teaching strategies and the classroom environment. Implications for educators and policy makers are discussed.
Keywords: Creativity in education, classroom strategies, student engagement, creative thinking, teaching methods, problem-solving skills.